A Constraint-Based Model for Fast Post-Disaster Emergency Vehicle Routing - Amadini, Roberto; Sefrioui, Imane; Mauro, Jacopo; Gabbrielli, Maurizio (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
Disasters like terrorist attacks, earthquakes, hurricanes, and volcano eruptions are usually unpredictable events that affect a high number of people. We propose an approach that could be used as a decision support tool for a post-disaster response that allows the assignment of victims to hospitals and organizes their transportation via emergency vehicles. By exploiting the synergy between Mixed Integer Programming and Constraint Programming techniques, we are able to compute the routing of the vehicles so as to rescue much more victims than both heuristic based and complete approaches in a very reasonable time.
Keywords: disaster recovery; decision support systems; constraint programming; mixed integer programming; IJIMAI